Efektifitas Ekstrak Pektin dari Kulit Buah Pisang Kepok (Musa paradisiaca Formatypica) Sebagai Antimikroba - Anwar, Amirah Faizah; Azis, A. Asmawati (Fakultas MIPA UNM, 2018)
Abstract. The research purpose to determine the antimicrobial activity of the extract pectin from fruit peel kepok banana (Musa paradisiaca formatypica). The extraction of pectin from banana peel kepok using conventional methods with 0.5 N hydrochloric acid solvent with factors consisting of pH (1.5 and 2.5) temperature (600C, 800C, 100 0C) and time (60, 90 and 120 minutes). This research was an experimental study using a completely randomized design (RAL) with factorial 2x3x3 3 times restating. The results yield a significant pectin is pH 2.5; temperature 1000C; and 120 minutes as much as 23.9%. The main factors were statistically significant influence on the results of pectin that is the interaction between pH and temperature, the interaction between temperature and time of extraction, and the interaction of pH, temperature, and time of extraction. Then do the phytochemical screening, to determine the content of secondary metabolites contained in the extract pectin from banana peel kepok. Test of antimicrobial activity using the paper disk. The microbes used in this research were Escherichia coli, Staphylococcus aureus and Candida albicans. Antimicrobial activity test results were analyzed by analysis of variance (ANOVA) and Tukey test then with the average difference (Î± = 0.05). Results of phytochemical screening rind extract pectin from kepok banana (Musa paradisiaca formatypica) contains flavonoids and saponins. The results of the antimicrobial activity of the extract pectin from banana peel kepok showed antimicrobial activity on Escherichia coli and the fungus Candida albicans then Staphylococcus aureus there does not showed antimicrobial activity because there was no blocked zone on paper disk area. Keywords: extract pectin from fruit peel kepok banana (musa paradisiaca formatypica), phytochemical screening, antimicrobial activity.